Evaluation of taste-masking effects of pharmaceutical sweeteners with an electronic tongue system. (March 2014) - Choi, Du Hyung; Kim, Nam Ah; Nam, Tack Soo; Lee, Sangkil; Jeong, Seong Hoon
Abstract Electronic tongue systems have been developed for taste measurement of bitter drug substances in accurate taste comparison to development palatable oral formulations. This study was to evaluate the taste masking effect of conventional pharmaceutical sweeteners such as neohesperidin dihydrochalcone, sucrose, sucralose and aspartame. The model drugs were acetaminophen, ibuprofen, tramadol hydrochloride, and sildenafil citrate (all at 20 mM). The degree of bitterness was measured by a multichannel taste sensor system (an electronic tongue). The data was collected by seven sensors and analyzed by a statistical method of principal components analysis (PCA). The effect of taste masking excipient was dependent on the type of model drug. Changing the concentration of taste masking excipients affected the sensitivity of taste masking effect according to the type of drug. As the excipient concentration increased, the effect of taste masking increased. Moreover, most of the sensors showed a concentration-dependent pattern of the taste-masking agents as higher concentration provided higher selectivity. This might indicate that the sensors can detect small concentration changes of a chemical in solution. These results suggest that the taste masking could be evaluated based on the data of the electronic tongue system and that the formulation development process could be performed in a more efficient way.